Information technology and the transformation of industries: Three research perspectives - Kevin Crowston; Myers, Michael D. (Journal of Strategic Information Systems, 2004)
It is often claimed that information technology has the potential to transform entire industries. However, we find that very little IS research has been conducted at the industry level. Moreover, the small amount of research that has been conducted on IT and industries has been based largely on just one perspective of industries. Given the scale and potential impact of the changes that are happening at an industry level, we believe a concerted effort is needed to study this phenomenon. We propose a research agenda for studying IT and industries. We suggest three research perspectives for studying IT and industries: an economic perspective, an institutional perspective, and a socio-cultural perspective. Just as IS research that addresses these aspects at the organizational level has grown in recent years and contributed to our understanding of IS, so in this paper we argue that a similar broadening, as well as more studies, are needed at the industry level of analysis. Weprovide an example from the real estate industry to illustrate the usefulness of the three research perspectives.
Keywords: Information Technology; Real Estate